The Blur Sensation: Shadows of the Future - O'Doherty, Damian P. (Organization (London, England), 2008)
The paper raises the question of embodiment and disembodiment as modes of theorizing organization and essays that struggle to negotiate what we call `entrance' to Blur, an `anti-architectural' installation designed as a working media pavilion by the New York based architects Diller and Scofidio. In Blur the human body is displaced from its customary mode of being-in-the-world and is given chance to discover `media' in organization as transport and possible metamorphosis in thinking and being organization. It is difficult to escape `Blur'. As the paper proceeds the reader begins to experience the sense that Blur is everywhere in organization—media and outcome of organization and both a symptom and possible site for the treatment of its underlying theoretical and methodological aporias. Blur invites a kind of de-subjectivization that intensifies sensation and affect splitting the subject across different modalities of consciousness and perception that provides essential experience for thinking organization critically. In the absence of this incorporeal `en-trance' the paper argues we will remain victim of the tautologies and infinite regress that afflict current thinking in aesthetics and organization and which restrict its practice to an inherently conservative form of organization analysis.